Distortion optimisation of beam-welded industrial parts by means of numerical welding simulation. (21st December 2010) - Schwenk, Christopher; Rethmeier, Michael
One of the critical values for quality considerations of industrial parts is the welding induced distortion. Hence, the understanding of the responsible mechanisms and the optimisation of the processes in order to minimise and control these deformations are primary goals of the research activities. Because of the high experimental effort for such investigations the numerical calculation with FEM is a useful tool for supporting. This research paper deals with the numerical welding simulation of circumferential weld seams on different industrial parts. The welding induced distortions of a small (injection valve) and a medium size (automotive gearwheel) industrial part are investigated. All research activities concentrate on the optimisation of the weld plan because geometry modifications of the parts are much more expensive and complex to realise. The understanding of the fundamental thermomechanical mechanisms causing the deformations is reached by the application of FEM calculations. Additionally, the simulation enables a direct and simple way of checking different weld plan configurations in order to control them. The resulting numerically optimised weld plan for the demonstrator parts shows a reduction of the relevant deformations of the parts up to 35%.